Phraseological Units as Means of Subjective-Evaluative Categorization on Scale ‘Confidence — Probability — Uncertainty — Approximation’ - L. V. Kalinina (Научный диалог, 2022)
The question is raised about the possibility of a systematic description of Russian phraseological units as a means of expressing a more or less confident categorization of objects and situations. The results of definitional, component and contextual analysis of 300 phraseological units are presented. The author’s classification of phraseological units into 4 groups is proposed: “confident categorization”, “most probable categorization”, “uncertain, borderline categorization”, “most approximate / ‘empty’ categorization”. It has been established that in most cases phraseological units express the speaker’s complete confidence in the categorization and evaluation of any objects or situations. It is noted that this confidence is often associated with the signs of ‘true / false’, ‘important / unimportant’, ‘similar / unlike’, ‘good / bad’. It was revealed that a smaller part of phraseological units characterizes the cases of the most probable, borderline and most approximate categorization. In general, the analysis shows that phraseological units most often verbalize such signs of a situation as its truth or falsity, the possibility or impossibility of establishing the truth, trust or distrust of the person from whom some information comes, which indicates the special importance of “truth” in the Russian language picture of the world.